Too much Facebook? An exploratory examination of social media fatigue. (March 2015) - Bright, Laura F.; Kleiser, Susan Bardi; Grau, Stacy Landreth
Highlights: This research examines social media fatigue and its proposed antecedents. Respondents with greater confidence experienced less social media fatigue. Respondents with greater privacy concerns experienced more social media fatigue. Social media helpfulness and social media fatigue are positively related. Respondents with greater self-efficacy experienced greater social media fatigue. Abstract: Social media usage levels continue to climb generating copious amounts of content. As more people crowd social media (e.g. Facebook), and create content, some research points to the existence of a concept called social media fatigue. Social media fatigue is defined as a user's tendency to back away from social media participation when s/he becomes overwhelmed with information. Lang's (2000) limited capacity model is used to understand the role of information overload for social media fatigue. This research examines the concept of social media fatigue and its proposed antecedents: social media efficacy, helpfulness, confidence and privacy concerns. Using confirmatory regression, this research determined that privacy concerns and confidence have the greatest predictive value for social media fatigue. This paper has theoretical implications for not only LCM but also other technology acceptance models such as TAM and UTAUT and UTAUT2. It also has implications for those trying to engage with online audiences and their subsequent reactions to that attempt at engagement. Several future research ideas are explored as well.